Proposing an Islamic-based alternative to dominant Western and Islamic teacher education models: An attempt at Curriculum improvement - Saheed Ahmad Rufai, (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper aims to compare the components of a newly proposed Islamic-based teacher education programme (IBTEP) model with those of dominant Western and Islamic teacher education models. The purpose of this comparison is to determine the degree of model adequacy for preparing teachers who will ultimately implement educational curricula in Islamic-based settings. The paper bases its analysis on four notable teacher education models: two Western two Islamic. The Western models are those of the Teachers College, Columbia University, and of University of Wisconsin-Madison. The two programs were selected because of their established reputations and their programmatic commonalities that are also inherent in most contemporary Western teacher education programmes, which often utilise the Tyler Model. The two Islamic models selected are those of the Jakarta, Indonesia State Institute for Higher Islamic Education (IAIN) and the International Islamic University Malaysia with a heavier emphasis on the latter because of its predominance in teacher education among contemporary Muslims. This paper is aimed towards curriculum improvement or programme reconstruction, employs curriculum criticism and analytic philosophy as its tools, and exposes both the strengths and deficiencies of the dominant Western and Islamic models for teacher education through a newly proposed IBTEP. The paper examines and analyzes the deficiencies of the aforementioned dominant Western and Islamic teacher education models for teaching and offers an IBTEP model as an ameliorative proposal for best practices in teacher education.